Análisis de dos diferentes tipos de mezclas TiO2 / carbón activado y su aplicación en métodos fotocatalíticos para la remoción de colorantes. (2020)
In this degree project, two types of mixture were analyzed, TiO2 / activated carbon composites and TiO2 supported on activated carbon that met the condition of photocatalysts for the removal of colorants by heterogeneous photocatalysis. In the same way, the sol-gel method, the hydrothermal method and the chemical vapor deposition were analyzed as methods of preparation of these two types of mixture and their influence on the photocatalytic activity. Some articles that contain one of the two types of mixture and that are prepared by any of the methods mentioned above are chosen by bibliographic review and in order to evaluate the photocatalytic activity of the TiO2 / Activated Carbon catalysts, these articles use colorants such as Methylene blue, methyl orange and RhB are subjected to adsorption and photodegradation tests for a certain time and are followed by the spectrophotometric method to observe the behavior of each type of mixture. The degradation percentages of the dyes reported in the articles show that from 100% to 97% of the dye is removed; Since mixing TiO2 with a highly porous material such as activated carbon generates a synergistic effect between adsorption and degradation, which makes the activated carbon retain the contaminants on the surface and the semiconductor (TiO2) takes over the photocatalytic process.